Factors Affecting Happiness of a Public University Staff: Case of Qualitative Research - Nuray Turan (Journal of Economy Culture and Society)
Since the beginning of the 2000s, the study of positive organizational behavior and positive psychological capital in the field of positive psychology has increased in the context of working life, and the importance of happiness research has been recognized, and interest has increased in this field. However, while these studies were mostly focused on private sector employees, there was not much among public employees, especially among those working in public universities. Therefore, the purpose of this article is to reveal the factors that affect happiness at work of the academic and administrative staff of a public university. For this purpose, face to face interviews were conducted with 37 university staff, 23 academic and 14 administrative staff, using structured interview method. According to the results; the factors that affect happiness at work have become apparent as “personal, environmental, work-related attitudes, relationships and managerial factors”. Among these factors, the most important factor affecting happiness at work for academic staff is the attitude towards work, and the least important factor is related to working environment relations. The most important factor is the administrative factors for administrative staff, and the least important factor is the environmental factor. The findings include data sources for future research, and it is foreseen that private universities will provide a basis for this research and will benefit from it.